Resistance to chemotherapy: What are the risks for the reindeer industry? - Waller, P. J. (Rangifer, 1990)
Although no drug resistance has been reported so far for parasites of reindeer, it would be unwise to assume that this situation will remain the same indefinitely. It is important to consider the principles of selection for resistance and plan ways of limiting these so that the emergence of resistance can be avoided.